POLITIK HUKUM DALAM PEMBENTUKAN KOMPILASI HUKUM ISLAM - Fina Wildaniyah; Ahmad Muktafi (Sekolah Tinggi Ilmu Syariah Abu Zairi Bondowoso, 2025)
The Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) is a legal product that emerged from the dynamics of Indonesian legal politics during the New Order era and became a crucial milestone in the unification of family law for Muslims in Indonesia. Its formation was rooted in the urgent need for a codified and uniform legal reference within the Religious Courts, considering that previously judges relied on various classical fiqh texts, which often resulted in inconsistent rulings. The KHI not only functions as positive law through Presidential Instruction No. 1 of 1991 but also serves as a means of harmonizing Islamic jurisprudential traditions with the national legal system. Nevertheless, its emergence triggered both support and criticism. Proponents argued that the KHI successfully addressed the demand for legal unification and expedited the settlement of cases in the Religious Courts. Critics, however, highlighted its weak legal standing, as it was established merely by presidential instruction rather than through formal legislation, and warned that it could limit the scope of judicial ijtihad. Despite such debates, the establishment of the KHI was regarded as a strategic step in the politics of Islamic law in Indonesia, especially under a political climate that was less accommodating to Islamic aspirations. The drafting process involved scholars, judges, and legal practitioners, who examined classical fiqh literature, judicial precedents, and comparative legal studies from other Muslim-majority countries. Thus, the KHI represents not only an attempt at codifying Islamic law in Indonesia but also a political-legal compromise between the aspirations of the Muslim community and the state’s political configuration. Ultimately, the KHI has served as a juridical reference to uphold legal certainty, utility, and justice for Muslims in Indonesia.